People.Food.Love / Nor Azila Azhar - Azhar, Nor Azila (2019)
Alhamdulillah, I most grateful to Allah S.W.T for the completion of this Social Media portfolio as one of the requirement that need to be accomplish in the course work assessment for the code ENT 530. Special thanks to my parents in supporting us to complete this portfolio by help sell my business product. This portfolio has been prepared with the cooperation and support from many people. Besides, not to be forgotten to my lecturers which are Madam Hajah Zanariah and her kindness in helping me during the process of completion of this social media business work. She have given me a good service by providing useful information. Without her, I would not be able to complete this portfolio. Through these problems I manage to become more organize and mature in dealing with problems that occur during my business. This portfolio covers social media business using Facebook, sales revenue, creating soft sell, creating hard sell and create teaser to attract customer. Lastly, to those who had involved and contributed directly or indirectly to this portfolio, I am very grateful to them for the effort and initiative that they have shown in my business until successfully completed my portfolio report. I apologize to all other unnamed person who helped me various ways to complete this portfolio and we hope this social media business and portfolio report can give us little bit about Entrepreneurship world and fact about how to become an entrepreneur in future.